Penerapan Metode Clustering pada Penyakit Abses Berdasarkan Faktor Penyebab - Siti Mutoharoh Permata Ayunda; Akim M.H. Pardede; Magdalena Simanjuntak (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
An abcess is a collection of pus in an indefinite space in the body, an abscess can appear on the surface of the skin and can appear in the tissues of an organ. Abscesses occur due to an infectious process or from parasitic bacteria due to foreign bodies, such as splinters, bullet wounds, needles. Many patients come with complaints of pain, swelling, redness, fever and others. Therefore, to overcome this problem, it is necessary to take quick action to help reduce and deal with the problem of abscess disease among the community by using the clustering method do that it can help agencies in conducting socialization so that the communinty knows more about the factors that cause abscess disease and how to handle it. From this research courced at tha Binjai estate Health Center which consists of several variables, namely age, type of abscess disease data that often appears, the abscess disease data that often appears after doing the 2 cluster process is with age is 26-35 years, with the type of abscess disease is dental abscess, and the casual factor is not maintaining dental hygiene.